Associations between pigment epithelium‐derived factor, insulin resistance and high density lipoprotein. Issue 9 (19th April 2013) - Pek, S.; Tavintharan, S.; Woon, K.; Niyati, J.; Lim, S. C.; Sum, C. F.
Abstract Aims To measure serum pigment epithelium‐derived factor in control subjects with normal fasting glucose, and in subjects with impaired fasting glucose and those with newly diagnosed Type 2 diabetes, before treatment initiation, and to measure pigment epithelium‐derived factor prospectively in patients being treated with HDL‐raising therapy, niacin. Methods We enrolled 89 individuals attending an institutional health screen. Biochemical indices including lipids, homeostasis model assessment‐insulin resistance, high‐sensitivity C‐reactive protein and pigment epithelium‐derived factor were analysed in fasting blood. To validate the association between HDL and pigment epithelium‐derived factor, we analysed samples from a separate study cohort with low HDL, followed up for 12‐weeks while on niacin treatment. Secreted pigment epithelium‐derived factor from 3T3‐L1 adipocytes, after HDL treatment (24‐h), was measured using Western blot analysis. Results Mean (± sd) serum pigment epithelium‐derived factor was significantly higher in subjects with impaired fasting glucose [13.99 (± 3.06) μg/ml] and Type 2 diabetes [12.94 (± 2.61)] μg/ml, compared with control subjects [11.83 (± 2.85) μg/ml (P = 0.014)]. In multivariate analyses, serum pigment epithelium‐derived factor concentration was associated with BMI (β = 0.32, 0.007), homeostasis model assessment‐insulin resistance (β = 0.33, P = 0.01) and HDL (β = −0.24, P = 0.05), after adjustment for age, gender and high‐sensitivity C‐reactive protein. In the niacin study, on‐treatment HDL was an independent determinant of pigment epithelium‐derived factor (β = −0.439, P = 0.033), after adjusting for age, homeostasis model assessment‐insulin resistance and treatment. Adipocytes treated with HDL were found to have reduced pigment epithelium‐derived factor secretion [24.8% (50 μg/ml), 28.4% (100 μg/ml) HDL; P < 0.05)], compared with the control samples. Conclusion Serum pigment epithelium‐derived factor is positively associated with homeostasis model assessment‐insulin resistance and negatively associated with HDL. Further studies are needed to understand the mechanism of low HDL and raised pigment epithelium‐derived factor and to determine if they are causally related to the pathobiology of insulin resistance.